PENGOLAHAN LIMBAH CAIR INDUSTRI TAHU DI DESA KALISARI KECAMATAN CILONGOK DENGAN METODE MULTI SOIL LAYERING - Irmanto Irmanto; Suyata Suyata (Molekul, 2009)
Tofu industry is one of the industries which causing pollution on the environment especially water environment. The amount of wastewater-dumped and the content of organic substances could damage the water ecosystem. Multi Soil Layering (MSL) as one of alternative method is used in order to remove the tofu industrial wastewater pollution. MSL is a method of wastewater treatment that enhances the function of soils to purify wastewater.The research aimed to determine optimum loading rate and efficiency of MSL system to remove TSS, BOD and COD. The wastewater on the MSL system is loaded at the loading rate varieties, i.e: 160, 320, 480, 640, and 800 lm-2 day-1, and the aeration was applied for 8 a day at 1296 ld-1.The results revealed that optimum loading rate was 320 lm-2 day-1 and efficiency of MSL system to remove TSS, BOD and COD were 78.62 % ; 98,89% and 95,53 % respectively.